2000
DOI: 10.1021/jf990594t
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antioxidative Activity of Propolis Evaluated by the Interaction with Vitamins C and E and the Level of Lipid Hydroperoxides in Rats

Abstract: In vivo antioxidative activity of propolis was evaluated on the basis of ameliorative effects on the oxidative stress induced by vitamin E deficiency in rats. The control group was fed vitamin E-deficient diet, and the propolis group was fed vitamin E-deficient diet supplemented with 1% of propolis for 4 and 8 weeks. Comparisons were made in tissue concentrations of vitamin C, vitamin E, and lipid hydroperoxides between these groups. No significant difference was observed in tissue vitamin E concentration betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 34 publications
3
27
0
8
Order By: Relevance
“…[34][35][36] Our results also show that honey is able to reduce the generation of lipid hydroperoxide. This is consistent with results reported by Sun et al 37 that propolis (a resinous material collected by bees from gum exudates of trees) could reduce levels of lipid hydroperoxides in vitamin E-deficient rats. In general, it has been reported that honey can prevent deteriorative oxidative reactions in foods, such as lipid oxidation.…”
Section: Discussionsupporting
confidence: 93%
“…[34][35][36] Our results also show that honey is able to reduce the generation of lipid hydroperoxide. This is consistent with results reported by Sun et al 37 that propolis (a resinous material collected by bees from gum exudates of trees) could reduce levels of lipid hydroperoxides in vitamin E-deficient rats. In general, it has been reported that honey can prevent deteriorative oxidative reactions in foods, such as lipid oxidation.…”
Section: Discussionsupporting
confidence: 93%
“…Due to its antioxidative effects, propolis may protect humans from deleterious oxidative processes. Several groups of authors thus studied the antioxidative properties of propolis and their active constituents [33][34][35] . Propolis may also act as a scavenger against oxygen radicals.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is probably due to the antioxidant protective effect of propolis which could have accumulated in the cells of the proximal convoluted tubules of the kidney where propolis was reported to be collected and secreted [156]. Osman and Tantaway [157] observed that oral administration of propolis extracts to rabbit significantly protected against histopathological alterations induced by gentamicin.…”
Section: Propolismentioning
confidence: 99%